Mus81 cleavage of Holliday junctions: a failsafe for processing meiotic recombination intermediates? - Gaskell, L; Osman, F; Gilbert, R; Whitby, M (2007)
The Holliday junction (HJ) is a central intermediate of homologous recombination. Its cleavage is critical for the formation of crossover recombinants during meiosis, which in turn helps to establish chiasmata and promote genetic diversity. Enzymes that cleave HJs, called HJ resolvases, have been identified in all domains of life except eukaryotic nuclei. Controversially, the Mus81-Eme1 endonuclease has been proposed to be an example of a eukaryotic nuclear resolvase. However, hitherto little or no HJ cleavage has been detected in recombinant preparations of Mus81-Eme1. Here, we report the purification of active forms of recombinant Schizosaccharomyces pombe Mus81-Eme1 and Saccharomyces cerevisiae Mus81-Mms4, which display robust HJ cleavage in vitro, which, in the case of Mus81-Eme1, is as good as the archetypal HJ resolvase RuvC in single turnover kinetic analysis. We also present genetic evidence that suggests that this activity might be utilised as a back-up to Mus81-Eme1's main activity of cleaving nicked HJs during meiosis in S. pombe.